STUDI KOMPARASI METODE PEMBELAJARAN BAHASA ARAB DAN HASIL BELAJAR BAHASA ARAB DI PONDOK PESANTREN MODERN DAN TRADISIONAL KABUPATEN JAMBI - Afriansyah Afriansyah (Universitas Nasional, 2018)
The aim of this research see the comparison of learning methods and the results of learning Arabicin the modern Al-Hidayah Islamic boarding school in Jambi City and the traditionalSa’adatuddaren Islamic boarding school in Jambi City. The subjects of the study is the head of themodern Al - Hidayah Islamic boarding school in Jambi City and the Jambi City Sa’adatuddarentraditional boarding school, Arabic language teachers in each pesantren and santri of each Islamicboarding school. Data collection technique is a method used by researcher to find data with using atype of qualitative research. Due to the method of learning Arabic in the modern Al-Hidayah Islamicboarding school in the city of Jambi and the traditional Sa’adatuddaren Islamic boarding school inthe city of Jambi has a difference and the learning objectives of each pesantren are different. Theresults of learning Arabic between the modern Al-Hidayah Islamic boarding school in the city ofJambi and the traditional Sa’adatuddaren Islamic boarding school in the city of Jambi there arealso clear differences. This is evidenced by the santri of modern Islamic boarding schools in moremodern Al - Hidayah Jambi City more able to communicate with Arabic and santri in the traditionalSa’adatuddaren Islamic boarding school in Jambi City more able to read and translate it, whenopening books using Arabic santri will be able to directly read and translate itKeywords: earning methods, learning outcomes, Arabic